ХАРАКТЕР РАСПРЕДЕЛЕНИЯ ШВ И IVB В "ВЫСОКИХ" И "НИЗКИХ" ВЕЗУВИАНАХ: ИНТЕРЕСНОЕ НАБЛЮДЕНИЕ ИЛИ ОШИБОЧНАЯ ИНТЕРПРЕТАЦИЯ АНАЛИТИЧЕСКИХ ДАННЫХ? - Галускин Е.В. (My University, 2006)
In the article of V. S. Kurazhkovskaya e. a. (Infrared spectra, unit cell parameters and optical character of boron-bearing vesuvianites and wiluites II Proceedins of RMO, 2005, N6, pp. 82-91) results of spectroscopic investigations are interpreted without sufficient application of published data on structure and crystal chemistry of the vesuvianite group minerals. The principal authors' conclusion: «boron occupies only triangle positions in low vesuvianites, in the high ones it may be in co-ordinations three and four», looks quite doubtfully. Investigators of vesuvianites know that it is practically impossible to resolve problems of the boron coordination without monocrystal infrared (IR) study, with considering polarization of bands (Groat e. a., 1995; Bellatreccia e. a., 2005). The authors' statement about increase of the unit cell parameters of boron-bearing vesuvianites due to replacement of hydrogen by larger boron (Kurazhkovskaya e. a., 2005, p. 88) has not any confirmation just in the field of monocrystal structural study of vesuvianites (Ohkawa, 1994; Groat e. a., 1996; Galushkin, 2005). In the whole, interpretation of trends in changing of unit cell parameters and optical character becomes quite doubtful. Probably, reasons of those changes in vesuvianites should be connected not only with crystal-chemistry of boron, but with some other elements, for instance, magnesium.
Keywords: 549.619.1:546.27(0.49.2)